2016
DOI: 10.1111/anae.13465
|View full text |Cite
|
Sign up to set email alerts
|

A randomised cross-over comparison of the transverse and longitudinal techniques for ultrasound-guided identification of the cricothyroid membrane in morbidly obese subjects

Abstract: A randomised cross-over comparison of the transverse and longitudinal techniques for ultrasound-guided identification of the cricothyroid membrane in morbidly obese subjects SummaryWe compared the transverse and longitudinal approaches to ultrasound-guided identification of the cricothyroid membrane, to determine which was faster and more successful. Forty-two anaesthetists received a one-hour structured training programme consisting of e-learning, a lecture and hands-on training, and then applied both techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 30 publications
2
54
0
2
Order By: Relevance
“…). However, pre‐procedural ultrasound scanning could assist in identifying the cricothyroid membrane more accurately, especially in obese patients . The Ambu‐aScope (single‐use flexible intubation scope) was used to determine correct tracheal tube placement within the trachea and to visualise false passage creation.…”
Section: Discussionmentioning
confidence: 99%
“…). However, pre‐procedural ultrasound scanning could assist in identifying the cricothyroid membrane more accurately, especially in obese patients . The Ambu‐aScope (single‐use flexible intubation scope) was used to determine correct tracheal tube placement within the trachea and to visualise false passage creation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that learning curves might be affected by the different techniques. However, the same authors showed the success rate between techniques were similar [26]. Lastly, we also performed the ultrasound scan in a controlled non-stressful environment.…”
Section: Discussionmentioning
confidence: 87%
“…In our study ultrasound scans were assessed using the longitudinal technique. Kristensen et al demonstrated the transverse technique was significantly faster than the longitudinal technique to identify the cricothyroid membrane [26]. It is possible that learning curves might be affected by the different techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Kristensen et al compared the transverse and longitudinal approach to ultrasoundguided identification of the cricothyroid membrane, to determine which was faster and more successful, utilising a one-hour training program consisting of e-learning, a lecture and hands-on training. Both approaches were associated with high success rates, though it was faster with the transverse approach [5].…”
Section: Through a Glass Darkly -Ultrasound Imaging In Obstetric Anaementioning
confidence: 96%
“…Pre-operative frailty in patients has been linked with increased postoperative morbidity [5], including delirium [6], sepsis [7], prolonged hospital stay [5] and postoperative re-admission [8], compared with non-frail counterparts. Moreover, Fried et al [4] suggest that frail patients may also suffer from a 'vulnerability to stressors'.…”
Section: Editorialmentioning
confidence: 99%